Stochastic differential equation harvesting models: sustainable policies and profit optimization - Brites, Nuno M. (2018)
We describe the growth dynamics of a fish or some other harvested population in a random environment using a stochastic differential equation ; general model, where the harvest term depends on a constant or on a variable fishing effort. We compare the profit obtained by the fishing activity with two types of harvesting policies, one based on variable effort, which is inapplicable, and the other based on a constant effort, which is applicable, sustainable and is socially advantageous. We use real data and consider a logistic and a Gompertz growth models to perform such comparisons. For both optimal policies, profitwise comparisons are also made when considering a logistic-type growth model with weak Allee effects. The mean and variance of the first passage times by a lower and by an upper thresholds are studied and, for a particular threshold value, we estimate the probability density function of the first passage time using the inversion of the Laplace transform; Resumo: MODELOS DE PESCA USANDO EQUAÇÕES DIFERENCIAIS ESTOCÁSTICAS: POLÍTICAS SUSTENTÁVEIS E OTIMIZAÇÃO DO LUCRO A dinâmica de crescimento de uma população sujeita a pesca em ambiente aleatório é descrita através de modelos de equações diferenciais estocásticas, onde o termo de captura depende de um esforço de pesca constante ou variável. Comparamos o lucro obtido pela atividade de pesca usando dois tipos de políticas de pesca, uma inaplicável e baseada em esforço variável e a outra aplicável, sustentável e socialmente vantajosa, baseada em esforço constante. As comparações são realizadas recorrendo a dados reais e considerando dois modelos de crescimento, o modelo logístico e o modelo de Gompertz. Para ambas as políticas ótimas, as comparações do lucro também são feitas quando se considera um modelo de crescimento do tipo logístico com efeitos de Allee fracos. A média e a variância dos tempos de primeira passagem por um limite inferior e por um limite superior são estudados e, para um determinado valor limite, estimamos a função de densidade do tempo de primeira passagem usando a inversa da transformada de Laplace.